AHRR (cg05575921) hypomethylation marks smoking behaviour, morbidity and mortality. Issue 7 (18th January 2017) - Bojesen, Stig E; Timpson, Nicholas; Relton, Caroline; Davey Smith, George; Nordestgaard, Børge G
Abstract : Rationale and objectives: Self-reported smoking underestimates disease risk. Smoking affects DNA methylation, in particular the cg05575921 site in the aryl hydrocarbon receptor repressor (AHRR ) gene. We tested the hypothesis that AHRR cg05575921 hypomethylation is associated with risk of smoking-related morbidity and mortality. Methods: From the Copenhagen City Heart Study representing the Danish general population, we studied 9234 individuals. Using bisulphite treated leucocyte DNA, AHRR (cg05575921) methylation was measured. Rs1051730 ( CHRN3A ) genotype was used to evaluate smoking heaviness. Participants were followed for up to 22 years for exacerbations of COPD, event of lung cancer and all-cause mortality. Six-year lung cancer risk was calculated according to the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial (PLCOM2012 ). Measurements and main results: AHRR (cg05575921) hypomethylation was associated with former and current smoking status, high daily and cumulative smoking, short time since smoking cessation (all p values <7×10 –31 ), and the smoking-related CHRN3A genotype (−0.48% per T-allele, p=0.002). The multifactorially adjusted HRs for the lowest versus highest methylation quintiles were 4.58 (95% CI 2.83 to 7.42) for COPD exacerbations, 4.87 (2.31 to 10.3) for lung cancer and 1.67 (1.48 to 1.88) for all-cause mortality. Finally, among 2576 high-risk smokers eligible for lung cancer screening by CT, observed cumulative incidences of lung cancer after 6 years for individuals in the lowest and highest methylation quintiles were 3.7% and 0.0% (p=2×10 –7 ), whereas predicted PLCOM2012 6-year risks were similar (4.3% and 4.4%, p=0.77). Conclusion: AHRR (cg05575921) hypomethylation, a marker of smoking behaviour, provides potentially clinical relevant predictions of future smoking-related morbidity and mortality.